Centronuclear myopathy related to dynamin 2 mutations: Clinical, morphological, muscle imaging and genetic features of an Italian cohort - Catteruccia, Michela (Pergamon Press, 2013)
Mutations in dynamin 2 (DNM2) gene cause autosomal dominant centronuclear myopathy and occur in around 50% of patients with centronuclear myopathy. We report clinical, morphological, muscle imaging and genetic data of 10 unrelated Italian patients with centronuclear myopathy related to DNM2 mutations. Our results confirm the clinical heterogeneity of this disease, underlining some peculiar clinical features, such as severe pulmonary impairment and jaw contracture that should be considered in the clinical follow-up of these patients. Muscle MRI showed a distinct pattern of involvement, with predominant involvement of soleus and tibialis anterior in the lower leg muscles, followed by hamstring muscles and adductor magnus at thigh level and gluteus maximus. The detection of three novel DNM2 mutations and the first case of somatic mosaicism further expand the genetic spectrum of the disease.